The Effect Of Feeding Additional Food (PMT) Ice Cream Made From Tilapia On Weight Changes In Toddler Lack Of Nutrition In Ciakar Village, Cipaku District Ciamis District - Nurhandayani, Vira; Lia Herliana; Sariestya Rismawati (Poltekkes Kemenkes Tasikmalaya, 2025)
Supplementary Feeding (PMT) is an intervention program for malnourished children to improve nutritional status according to their age. The prevalence of malnourished children in Indonesia has not changed since 2016-2017, which is 17.8% but in 2018, the prevalence fell to 13.8%. Objective: to determine the effect of tilapia fish on changes in toddler weight at the age of 12 months - 59 months. Method: This study used the Quasi-experimental with control group method with a totaling sample sampling technique of 36 toddlers with 18 toddlers in the experimental group and 18 toddlers in the control group. The data processing technique used the paired t-test with normal data distribution. Results: The results of the study showed a significant difference in toddler weight before and after being given tilapia ice cream with the group that was not given treatment. Where the results of the hypothesis test Weight before and after being given treatment sig.2- tailed <0.05 so that it can be concluded that there is a significant effect on the provision of tilapia ice cream in the experimental group. The sig 2-tailed value <0.05 in the control group so it can be concluded that there is also an effect on the control group without giving tilapia ice cream. So it can be concluded that there is an effect of giving tilapia ice cream on toddlers' weight before and after being given